Correlation of Administrative Definitions of Refugees and Internally Displaced Persons: Compliance with International Standards - Gerasymenko, Yevgen; Zadyraka, Nataliia; Georgiievska, Viktoriia; Kovalenko, Nataliia; Leheza, Yulia (The Age of Human Rights Journal, 2022)
The purpose of this study is to investigate the correlation of administrative definitions of refugees and internally displaced persons, as well as compliance of these definitions with international standards. The methodological framework of the study included analytical, legal, and statistical methods of analysis. The study employed general scientific and special methods of cognition. The paper investigates the main provisions of the legislative framework at the international and national levels. The applied methods allowed obtaining reliable and reasonable conclusions and results. Therefore, it is necessary to legislatively regulate the situation of persons who have been in Ukraine for a long time in violation of the law. The specified non-conformity of the legislation of Ukraine should be eliminated in two parallel ways. The specified non-conformity of the legislation of Ukraine should be eliminated in two parallel ways. On the one hand, any restrictions on the circle of persons to whom it applies should be excluded from the definition of IDPs in Article 1 of the Law of Ukraine “On Ensuring the Rights and Freedoms of Internally Displaced Persons”, primarily regarding the presence of stateless persons on the territory of Ukraine on legal grounds and the right to permanent residence in Ukraine. On the other hand, the corresponding law approves the procedure for determining a person as stateless, or apatride. This paper presents the criteria for the correlation between the terms “refugee” and “internally displaced person”. The practical value of this study lies in the fact that the investigation of the correlation of administrative definitions of refugees and internally displaced persons and their compliance with international standards is essential for practitioners and theorists in legal science.